Blinky Bill and the rabbit's birthday party - Odell, Carol (Angus and Robertson, 1971)
Blinky Bill greatly enjoys himself at a rabbit's birthday party but when he pulls Madam Hare's tail a fight breaks out and he is forced to leave.